Image-guided high-dose-rate brachytherapy in inoperable endometrial cancer - Dankulchai, P (The British Institute of Radiology., 2014)
Inoperable endometrial cancer may be treated with curative aim using radical radiotherapy alone. The radiation techniques are external beam radiotherapy (EBRT) alone, EBRT plus brachytherapy and brachytherapy alone. Recently, high-dose-rate brachytherapy has been used instead of low-dose-rate brachytherapy. Image-guided brachytherapy enables sufficient coverage of tumour and reduction of dose to the organs at risk, thus increasing the therapeutic ratio of treatment. Local control rates with three-dimensional brachytherapy appear better than with conventional techniques (about 90–100% and 70–90%, respectively).